DESAIN SIMULASI UNJUK KERJA KODE SMALL KASAMI PADA KANAL MULTIPATH FADING - I Kadek Adi Wiguna Sanjaya; Nyoman Pramaita; I Made Oka Widyantara (Jurnal SPEKTRUM, 2021)
Telecommunication capable of handling interference, fading and no less importantissues regarding the confidentiality of user information is very much needed in the currenttechnological era, to overcome this spread spectrum technology is quite developed in theadvancement of telecommunication technology. In this study, the small kasami code was usedas the spreading code. The purpose of this study is to determine the performance of the smallkasami code with changes in the number of multipath components using multipath fadingchannels. The modulation technique uses digital modulation, namely binary phase shift keying(BPSK) with a small kasami code with a code length of 15 in the spreading and spreadingprocess. Analyzed based on BER (Bit Error Rate) versus EB/No (Energy Bit per Noise). In thesimulation of flat fading performance using 1 multipath component, flat fading serves as an idealreference where the simulation BER should resemble the theoretical BER as simulationvalidation so that it can be used on selective fading channels. Variation of multipathcomponents in frequency selective fading channel produces different BER because there isinterference of multipath signal to the desired signal. The number of multipath components asmany as 11 have the most interference signals resulting in the worst performance. The value ofcross correlation between users has poor performance, where the correlation value of user 1with 2, 3, and 4 is more than 0, this value shows that many signal levels experience interferencebetween users.